Perbandingan Hukum mengenai Narkotika antara Indonesia dan Malaysia - Abdul Haris Nafis; Handar Subhandi Bakhtiar (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The problem of drug abuse is a serious challenge in various countries, including Indonesia and Malaysia. Both countries have strict legal systems in dealing with drug crimes, with an approach that emphasizes the imposition of severe criminal sanctions on perpetrators. This study aims to compare drug law policies between Indonesia and Malaysia, especially in terms of regulation, law enforcement, and the types of criminal sanctions applied. The research method used is normative juridical with a comparative legal approach between countries. The results of the study show that although in general both countries adopt a repressive approach, there are important differences in their legal systems. Malaysia applies a mandatory death penalty for drug dealers in certain amounts, as regulated in the Dangerous Drugs Act 1952. Meanwhile, Indonesia gives judges the authority to determine the type of sanctions, including the death penalty, based on legal considerations and justice in Law No. 35 of 2009. This study is expected to be an evaluation material for policy makers in Indonesia in formulating a drug law system that is not only repressive, but also pays attention to aspects of justice, human rights, and legal effectiveness.